2021
DOI: 10.1177/23978473211049085
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary ammonium compounds: perspectives on benefits, hazards, and risk

Abstract: Quaternary ammonium compounds are antimicrobial chemicals that provide significant public health benefits by controlling bacteria and viruses that cause infections such as colds, flu, and COVID. The benefits of antimicrobial QACs are seen in increased quality-of-life measures, such as reduced time away from work and school and reduced medical costs. As active antimicrobial agents, QACs and QAC-containing consumer and professional products are highly regulated by authorities such as the US Environmental Protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
(71 reference statements)
0
15
0
Order By: Relevance
“…No occupational or general population HBELs have been established by the U.S. Occupational Safety and Health Administration (OSHA), ACGIH, or the Occupational Alliance for Risk Science‐Workplace Environment Exposure Levels (OARS‐WEEL) Committee. Based on robust, good laboratory practices (GLP) studies, QACs are expected to be generally safe when used as directed, with no evidence of dermal sensitization, genotoxicity, mutagenicity, carcinogenicity, systemic toxicity, or developmental or reproductive toxicity; however, irritation and corrosive effects are possible depending on use concentration and use 14–16,39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No occupational or general population HBELs have been established by the U.S. Occupational Safety and Health Administration (OSHA), ACGIH, or the Occupational Alliance for Risk Science‐Workplace Environment Exposure Levels (OARS‐WEEL) Committee. Based on robust, good laboratory practices (GLP) studies, QACs are expected to be generally safe when used as directed, with no evidence of dermal sensitization, genotoxicity, mutagenicity, carcinogenicity, systemic toxicity, or developmental or reproductive toxicity; however, irritation and corrosive effects are possible depending on use concentration and use 14–16,39 …”
Section: Discussionmentioning
confidence: 99%
“…Safety assessments of some ethanol uses—such as in hand scrubs—have demonstrated minimal concern due to appropriate margins between exposure and health guidelines based on blood alcohol concentrations 12,13 . The toxicology profile for QACs has also been well described and shows QACs are safe when used as directed 14–16 . However, several studies have reported the use of various products that contain QACs are associated with allergic or irritant asthma and contact dermatitis among healthcare, food preparation, floor cleaning, and cleaning workers, as well as the general public 11,17–21 .…”
Section: Introductionmentioning
confidence: 99%
“…4 ). Several studies have reported the effectiveness of QACs against influenza and SARS viruses ( Schrank et al, 2020 , Osimitz and Droege, 2021a , Dellanno et al, 2009 ). These compounds can target intracellular genetic materials such as single-stranded RNA, in the case of SARS-CoV-2.…”
Section: Classification Mechanism Of Action and Applications Of Qacsmentioning
confidence: 99%
“…Although these compounds have been used for many years, supposedly safely, there are still some controversies today about whether the short or prolonged exposure to this product is not harmful to human or animal health, or whether the waste produced is friendly to the environment. Thus, we have on one side several studies comprising an extensive amount of data on QACs supporting their safe use in a variety of applications [3,4], and on the other side, we have studies on the potential harm to human health, animals and the environment due to the use of this type of compounds [5,6]. We can cite as an example a study published in Nature in which the negative effect provoked by these chemicals is evidenced when they were used for cleaning mice's cages, causing birth and fertility alterations [7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, after the identification of the SARS-CoV-2 virus as responsible for the COVID-19 outbreak, the EPA (U.S. Environmental Protection Agency) published a list of effective surface disinfectants in the fight against SARS-CoV-2, which until the Spring 2021 included 551 disinfectants, of which approximately 34% contained QACs, highlighting the importance of these compounds to public health during the pandemic [6]. Among the QACs, the ADBAC (Alkyl Dimethyl Benzyl Ammonium Chloride) and DDAC (Didecyl dimethyl ammonium chloride) compounds have the highest number of active records, which are the main ingredients of the fifth generation quaternary ammonium (5GQA) [8].…”
Section: Introductionmentioning
confidence: 99%